Classifying Cockroaches According to Forewings: Pitfalls and Implications for Fossil Systematics - Xin-Ran Li (Taxonomy)
A reliable character system is crucial to taxonomy and systematics, and it promises valid downstream inferences, e.g., estimates of diversity and disparity, reconstruction of evolutionary history, and even stratigraphic correlations. Modern taxonomy and systematics of extant cockroaches requires an integrative study involving multiple lines of evidence with emphasis on genital and reproductive characteristics and molecular data. In contrast, many fossil cockroach taxa published recently are based solely on forewings. Many studies have shown that forewing-based taxa are questionable. In order to find out how much of the phylogenetic signal we could ascertain from venational similarity, and how confident we could be, this study used forewing characters to reconstruct phylogenies of the genera of well-recognized family-group taxa. The intuitively reconstructed phylogeny of 75 extant genera failed to recover those taxa or their relationships. Parsimony analyses of various datasets all yielded strong polyphyly and chaotic relationships. In conclusion, the forewing of cockroaches is not a universally competent character system. The underlying causes are the complicated nature of veins and the limitations of current analytical techniques. The uncertainty in forewing-based taxonomy and systematics has been underestimated in the literature. Forewing-based fossil taxa warrant re-evaluation; some of them are herein deemed nomina dubia in their current state.